Comparative analysis of urea and nano urea along with zinc fertilization on yield and nutrient uptake in wheat (Triticum aestivum) - REDDY, KADAPA SREENIVASA; SHIVAY, YASHBIR SINGH; KUMAR, DINESH; POONIYA, VIJAY; PRASANNA, RADHA; MANDI, SUNIL; NAYAK, SOMANATH; BARAL, KIRTTIRANJAN; ALEKHYA, GUNTURI; BORATE, ROHIT BAPURAO (The Indian Journal of Agricultural Sciences, 2025)
A study was carried out during winter (rabi) seasons of 2021–22 and 2022–23, at the ICAR-Indian Agricultural Research Institute, New Delhi to assess the effectiveness of different nitrogen sources combined with zinc fertilization on the yield and nutrient uptake by wheat (Triticum aestivum L.) in a split-plot design (SPD) with three replications. The experiment consisted of nitrogen (N) treatments in main plot (0 kg/ha, 130 kg/ha, 97.5 kg/ha + nano urea foliar sprays, 65 kg/ha + nano urea foliar sprays and 65 kg/ha + prill urea foliar sprays) and zinc (Zn) treatments in subplot (no Zn, 0.5% ZnSO4 foliar spray, 0.1% nano-ZnO foliar spray and cyanobacterial (BF1)-Anabaena spp.). This study revealed that tillers/m2, grain yield, straw yield, and N uptake increased by 19.8%, 27.7%, 28.3%, and 69.0%, respectively with nitrogen application of 130 kg/ha in comparison to control (0 kg/ha). However, nitrogen at 65 kg/ha + nano urea foliar spray reduced the grain yields by 10.1% and nitrogen uptake by 23.8% as compared to nitrogen application at 130 kg/ha over the two-year study period. Moreover, nitrogen application of 97.5 kg/ha + nano urea foliar spray had a statistically similar yield compared to 130 kg N/ha. Nano-zinc oxide applied at the rate of 0.1% foliar spray recorded significantly higher in wheat yields (4.1%) and Zn nutrient uptake (18%), compared to no Zn fertilization. Therefore, it may be recommended that nitrogen at 130 kg/ha combined with a foliar spray of 0.1% nano-zinc oxide at critical stages can be applied to enhance yields and nutrient uptake in wheat.